Customers’ Gratification and ISO 9001 Quality Management Practices Among Manufacturing Companies - Paul Olonade, Olanrewaju; Ametepe, Paul Kojo (Management Research Journal, 2023)
It is imperative to have a thorough awareness of the relationship between ISO 9001 quality management and customer satisfaction. It is on this basis that this study aims to analyze the link that exists between customer satisfaction and ISO 9001 Quality Management proxies by dedication to quality, employee participation, and fact-based management. The descriptive survey design was used for this study, and primary data were collected using a self-developed questionnaire from 630 randomly chosen respondents from a population of 17836 employees of 30 manufacturing companies in Lagos State, Nigeria. Deming’s Theory of Total Quality Management and Signaling Theory underpinned the study. The Statistical Package for Social Scientists (SPSS 21.0) was used to evaluate the four hypotheses raised using the Pearson Product Moment Correlation Coefficient at 0.05 significance level and multiple regression. The study found that dedication to quality, and employee participation have a significant positive relationship and good predictors of customer satisfaction among manufacturing companies. However, based on the study’s findings, fact-based-management did not have any influence on customer satisfaction. The study concludes that organizations should strive to conduct a continuous review of customers’ viewing orders to retain the customers by providing them with quality products through ISO 9001 while encouraging employee participation in its implementation.